Cultural discontinuity between home and school and American Indian and Alaska Native children's achievement. Issue 4 (4th July 2017) - Torres, D. Diego
ABSTRACT: An assumption of culture-based education with respect to American Indian and Alaska Native (AI/AN) children is that discontinuity between home and school cultures is responsible for educational underachievement. Using data from the 2009 round of the National Indian Education Study, a subset of the larger National Assessment of Education Progress (NAEP), the author constructed a measure of cultural discontinuity and examined its relationship to AI/AN students' Grade 4 and 8 reading and mathematics achievement. Contrary to the cultural discontinuity hypothesis, there is no statistically significant negative relationship when the culture of the home is discontinued at school. On the Grade 4 NAEP reading assessment, in particular, cultural discontinuity was positively associated with students' achievement, net of both student- and school-level controls. Findings suggest that the assumptions of culture-based education may be overstated, though longitudinal data are still needed to be able to make causal claims.